Power characteristics of the push movement in college judo athletes - Iteya, M.; Tomita, Y.; Yanagisawa, H.; Saito, S.; Kaneko, K. (Association for the Scientific Studies on Judo, Kodokan, 2011)
The purpose of this study was to investigate characteristics of physical power using a pushing b ar which was developed to measure power during practical movements in Judo. The bar is called a Dosukoi-bar named after a movement in Sumo. The subjects were College students, 9 male judo athletes and 11 male Track and Field (T&G) athletes. Two types of upper limb power were measured using a FITROdyne (S&C co.), pushing power from a Standing p o stu re and a bench press. Leg power was also measured using a power cycle (Power Max V; Combi Wellness Co.). Average powers per body weight in the judo group were compared with the T&F group. All of the average power for the Dosukoi-bar, bench press, and power cycle for the judo group was significantly lower th an the T&G group. It seemed th at the T&F group had larger muscular power because they conducted weight training regularly. The correlation was calculated to find the relationship between pushing power using the Dosukoi-bar and other variables for power. There was a significant correlation between pushing power and total power score (r=0.74, p<0.05) within the judo group. However, there was no significant correlation for the same variables within the T&G group (r = 0.31, p>0.05). It seemed that pushing power from standing posture was strongly related to upper and lower limb power for judo players. That is, judo players integrated pushing power by using the limb power better than T&G athletes.